Spontaneous Regression of Cardiac Rhabdomyoma Presenting as Severe Left Ventricular Inlet Obstruction in a Neonate with Tuberous Sclerosis - Eun Song Song; Kumi Jeong; Gun Kim; In Ji Hwang; Mi-Ji Lee; Hwa Jin Cho; Young Kuk Cho (Case Reports in Cardiology)
Cardiac rhabdomyoma can be subclinical or have a fatal presentation according to the onset age and involved site, size, and degree of invasion. Although most cardiac rhabdomyomas become smaller with time, emergency intervention is indicated when severe obstruction has occurred. In this report, we describe the spontaneous regression of a large cardiac rhabdomyoma (20.5 × 15.6 mm) presenting as severe left ventricular inlet obstruction in a neonate with tuberous sclerosis. Although a cardiac rhabdomyoma can be large enough to induce left ventricular inlet obstruction, conservative treatment without aggressive surgical intervention can be considered if the hemodynamic condition does not deteriorate.